Belajar Sambil Bermain: Menguak Strategi Pembelajaran Efektif untuk Anak Usia Dini - Nasthasya Numaseb (Montessori Jurnal Pendidikan Kristen Anak Usia Dini, 2025)
This study aims to examine effective learning strategies implemented through play-basedapproaches in early childhood education. The main issue addressed is how play activities canbe integrated into the learning process to enhance children's engagement and overalldevelopment. This descriptive qualitative research involved teachers and children aged 4–6years in an early childhood education setting. Data were collected through observation,interviews, and documentation. The findings indicate that learning through play increaseschildren’s interest in learning, social skills, and cognitive abilities. Effective strategies includethe use of educational play tools, imagination-based activities, and the active role of teachers inguiding children during play. This research highlights the importance of teacher competence indesigning structured yet enjoyable play activities as a foundation for early learning.